2018
DOI: 10.1021/acsnano.8b02161
|View full text |Cite
|
Sign up to set email alerts
|

Optical Gating of Graphene on Photoconductive Fe:LiNbO3

Abstract: We demonstrate experimentally nonvolatile, all-optical control of graphene's charge transport properties by virtue of an Fe:LiNbO photoconductive substrate. The substrate can register and sustain photoinduced charge distributions which modify locally the electrostatic environment of the graphene monolayer and allow spatial control of graphene resistivity. We present light-induced changes of graphene sheet resistivity as high as ∼370 Ω/sq (∼2.6-fold increase) under spatially nonuniform light illumination. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…[11] Gorecki et al demonstrated a graphene all-optical control device based on an Fe:LiNbO 3 substrate. [25] Sassi et al presented an uncooled mid-infrared photodetector based on graphene and a LiNbO 3 substrate. [26] A mid-infrared graphene photodetector based on a z-cut LiNbO 3 substrate was reported by Gopalan et al However, the responsivity of this photodetector device is less than 2 × 10 −4 A W −1 , and the response time is 1.3 s. [13] Baeumer et al [12] have reported a p-n junction transistor using graphene on a periodically poled z-cut LiNbO 3 substrate with a responsivity of 2 × 10 −5 A W −1 in the visible range.…”
Section: Doi: 101002/adom202100245mentioning
confidence: 99%
“…[11] Gorecki et al demonstrated a graphene all-optical control device based on an Fe:LiNbO 3 substrate. [25] Sassi et al presented an uncooled mid-infrared photodetector based on graphene and a LiNbO 3 substrate. [26] A mid-infrared graphene photodetector based on a z-cut LiNbO 3 substrate was reported by Gopalan et al However, the responsivity of this photodetector device is less than 2 × 10 −4 A W −1 , and the response time is 1.3 s. [13] Baeumer et al [12] have reported a p-n junction transistor using graphene on a periodically poled z-cut LiNbO 3 substrate with a responsivity of 2 × 10 −5 A W −1 in the visible range.…”
Section: Doi: 101002/adom202100245mentioning
confidence: 99%
“…Our approach also allows an alloptical 87% conductivity change in a 2D graphene layer obtained totally by optical means with exceptional efficiency of the graphene light-matter interaction (fluence 6 mJ/cm 2 ). Furthermore, the observed rate of conductivity change is at least 3 orders of magnitude faster than previously reported [25] and has potential for further improvement. This method opens the prospect for ultraefficient, all-optically-controlled 2D-FE devices incorporating electronic and photonic functionalities for memories, integrated photonics, sensors, and other optoelectronic applications, including a whole variety of possible combinations.…”
Section: Kundysatipcmsfrmentioning
confidence: 50%
“…2(a)] results in the large change of graphene resistance reaching 87% even with an extremely weak light power of 75 µW (fluence 6 mJ/cm 2 ) [Fig. 2(b)], greatly exceeding previous observations [23][24][25][26]. The light illumination decreases the electric field in the sample and hence the polarization [Fig.…”
Section: Optical Memory Effectmentioning
confidence: 86%
See 1 more Smart Citation
“…[31][32][33][34] The singlelayered graphene structure as a uniform platform provides a large specic surface area with binding points to interact with substrates and/or active metals, and may form strong p-p interlayer interactions for electrical or energy transfer. 35,36 Therefore, it has been explored in various elds, such as catalysts, [37][38][39][40][41][42][43] biosensors, [44][45][46][47][48] supercapacitor, [49][50][51] and Li-ion batteries. 52,53 Iridium named from the Greek goddess of the rainbow possesses some unique characteristics and has been extensively investigated in various elds such as organic light-emitting diode (OLED), 54,55 solar cells, 56,57 water splitting to produce hydrogen or oxygen, 58,59 and carbon dioxide reduction.…”
Section: Introductionmentioning
confidence: 99%